Direct chemical synthesis of well dispersed L10-FePt nanoparticles with tunable size and coercivity. Issue 2 (20th August 2015) - He, Jianghai; Bian, Baoru; Zheng, Qiang; Du, Juan; Xia, Weixing; Zhang, Jian; Yan, Aru; Liu, J. Ping
Abstract : We report a simple, green, one-step solid-phase approach to synthesize well-dispersed single-crystal L10 -FePt nanoparticles with coercivity of more than 20 kOe. Abstract : We report a simple, green, one-step solid-phase approach to synthesize well-dispersed single-crystal L10 -FePt nanoparticles with coercivity of more than 20 kOe. In this method, only Fe and Pt metal precursors are used in the absence of an organic solvent and surfactant, and a NaCl particle media is used both as substrate for nanoparticle nucleation and growth, and an insulation medium preventing nanoparticle coalescence during high temperature sintering. The chemically ordered L10 -FePt nanoparticles can be obtained at synthesis temperatures as low as 350 °C. The size of the FePt nanoparticles can be tailored from 7.2 nm to 15 nm and the coercivity at room temperature can be tuned from 3.15 kOe to 21.5 kOe depending on the synthesis temperatures. The elemental analysis shows a uniform distribution and 1 : 1 atomic ratio of Fe/Pt. The evolution of particle formation, phase transition, ordering parameter, particle size, and magnetic properties have been measured and analyzed by TG-DTA, XRD, TEM and MPMS at different synthesis temperatures from 300 °C to 750 °C. The nanoparticles synthesized by this method can be applicable in fields such as magnetism and catalysis.